2009
DOI: 10.3130/aijs.74.2245
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Heat-Mechanics Interaction Behavior of Laminated Rubber Bearings

Abstract: This paper describes the experimental study on heat-mechanics interaction behavior of laminated rubber bearings, such as lead rubber bearings (LRB) and high damping rubber bearings (HDB) under larger and more cyclic lateral deformation. For the rubber bearings installed to the base-isolated structures, the seismic energy they absorb is transformed into the thermal energy, so heat is generated causing high temperatures in the lead plug and high damping rubber. There are few experimental data so far, especially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Several studies developed models of seismic isolator behavior that can account for the deterioration of the isolator strength and stiffness due to repeated cycling as a result of hysteretic heating and other effects. 7,[17][18][19][20][21][22][23][24][25] Although these models are presumed useful for the study of the effects of long-duration motion on the response of seismically isolated structures and they have been available for some time, there are no studies that utilize these models and employ statistically healthy 26 large number of ground motions with a large range of motion duration to examine the seismic response of seismically isolated structures. The study reported in this paper attempts to do that by providing information on the effects of ground motion duration on response parameters that are relevant to (a) the design of seismically isolated buildings and (b) the testing of seismic isolators.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies developed models of seismic isolator behavior that can account for the deterioration of the isolator strength and stiffness due to repeated cycling as a result of hysteretic heating and other effects. 7,[17][18][19][20][21][22][23][24][25] Although these models are presumed useful for the study of the effects of long-duration motion on the response of seismically isolated structures and they have been available for some time, there are no studies that utilize these models and employ statistically healthy 26 large number of ground motions with a large range of motion duration to examine the seismic response of seismically isolated structures. The study reported in this paper attempts to do that by providing information on the effects of ground motion duration on response parameters that are relevant to (a) the design of seismically isolated buildings and (b) the testing of seismic isolators.…”
Section: Introductionmentioning
confidence: 99%
“…conducted coupled heat and structural analyses and compared the results with their test results. Takenaka et al 32 . reported an experimental study on coupled heat and mechanical behavior of laminated HDRBs.…”
Section: Introductionmentioning
confidence: 99%